Leptin attenuates cerebral ischemic injury in rats by modulating the mitochondrial electron transport chain via the mitochondrial STAT3 pathway. Issue 2 (10th January 2019) - Hu, Shijun; Cheng, Daobin; Peng, Dingtian; Tan, Jing; Huang, Yanlan; Chen, Chunyong
Abstract: Background: According to recent studies, leptin may exert a neuroprotective function by affecting the phosphorylation of signal transducer and activator of transcription 3 (STAT3). During stress, STAT3 regulates mitochondrial oxidative stress and reduces apoptosis. Objective: In the present study, we hypothesized that leptin increases STAT3 phosphorylation in the mitochondria and protects against mitochondrial oxidative stress in rats subjected to permanent middle cerebral artery occlusion (MCAO). Results: Leptin reduced reactive oxygen species (ROS) production, and we confirmed that the mechanism underlying this change involved the enzymatic activities of mitochondrial respiratory chain complexes I and II. In addition, leptin increased the level of STAT3 Ser727 phosphorylation in the mitochondria. Conclusions: Based on these results, leptin may regulate mitochondrial respiratory chain enzymatic activities via mitochondria‐targeted STAT3 to reduce ROS production and protect brain tissues from mitochondrial oxidative stress during cerebral ischemia. Abstract : Leptin reduced the production of reactive oxygen species (ROS). Leptin‐mediated reduction in ROS involved the enzymatic activities of mitochondrial respiratory chain. Leptin increased the level of STAT3 phosphorylation in mitochondria.